Identification of Whirly transcription factors in Triticeae species and functional analysis of TaWHY1-7D in response to osmotic stress - Liu, Hao; Wang, Xiaoyu; Yang, Wenbo; Liu, Wenyan; Wang, Yanfang; Wang, Qin; Zhao, Yanhong (Frontiers in Plant Science, 2023)
Osmotic stress poses a threat to the production and quality of crops. Whirly transcription factors have been investigated to enhance stress tolerance. In this study, a total of 18 Whirly genes were identified from six Triticeae species, which were classified into Whirly1 and Whirly2. The exon–intron structure, conserved motif, chromosomal location, collinearity, and regulatory network of Whirly genes were also analyzed. Real-time PCR results indicated that TaWHY1 genes exhibited higher expression levels in leaf sheaths and leaves during the seedling stage, while TaWHY2 genes were predominantly expressed in roots. Under PEG stress, the expression levels of TaWHY1-7A, TaWHY2-6A, TaWHY2-6B, and TaWHY2-6D were increased, TaWHY1-7D was reduced, and TaWHY1-4A had no significant change. All TaWHY genes were significantly up-regulated in response to NaCl stress treatment. In addition, TaWHY1-7A and TaWHY1-7D mainly enhanced the tolerance to oxidative stress in yeast cells. TaWHY2s mainly improved NaCl stress tolerance and were sensitive to oxidative stress in yeast cells. All TaWHYs slightly improved the yeast tolerance to d-sorbitol stress. The heterologous expression of TaWHY1-7D greatly improved drought and salt tolerance in transgenic Arabidopsis. In conclusion, these results provide the foundation for further functional study of Whirly genes aimed at improving osmotic stress tolerance in wheat.